2017
DOI: 10.1371/journal.pone.0172013
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of health-related physical fitness. The Portuguese sibling study on growth, fitness, lifestyle and health

Abstract: This study investigates biological, behavioural and sociodemographic correlates of intra-pair similarities, and estimates sibling resemblance in health-related physical fitness (PF). The sample comprises 1101 biological siblings (525 females) aged 9–20 years. PF components and markers were: morphological [waist circumference (WC) and %body fat (%BF)], muscular [handgrip strength (GS) and standing long jump (SLJ)], motor [50-yard dash (50YD) and shuttle run (SR)], and cardiorespiratory (1-mile run). Biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
1
9
1
2
Order By: Relevance
“…Another study carried out with 282 adolescents of both genders aged 11-13 years from three schools in southern Brazil (Londrina) found that 56% of boys and 34% of girls had inadequate levels of cardiorespiratory fitness, but boys presented higher VO 2 in relation to girls. A similar result was found by Pelegrini et al 19 in a study with 601 schoolchildren aged 14-17 years, also in southern Brazil (mid-western state of Santa Catarina), where boys had higher prevalence of inadequate VO 2 (92.6%) when compared to girls (35.5%), but the relative VO 2 was higher in males than in females 20 .…”
Section: Discussionsupporting
confidence: 86%
“…Another study carried out with 282 adolescents of both genders aged 11-13 years from three schools in southern Brazil (Londrina) found that 56% of boys and 34% of girls had inadequate levels of cardiorespiratory fitness, but boys presented higher VO 2 in relation to girls. A similar result was found by Pelegrini et al 19 in a study with 601 schoolchildren aged 14-17 years, also in southern Brazil (mid-western state of Santa Catarina), where boys had higher prevalence of inadequate VO 2 (92.6%) when compared to girls (35.5%), but the relative VO 2 was higher in males than in females 20 .…”
Section: Discussionsupporting
confidence: 86%
“…Within the sample, there were a small number of 16 and 17‐year‐old children. These were combined into the 15‐year‐old group, ie, 15+; for analysis, see Gomes et al Sample 3 consisted of 1745 children (859 boys) aged 7 to 17 years old, recruited as part of the Active Vouzela project in the midlands of Portugal (see Chaves et al). Sample 4 consisted of 2365 children (1197 boys) aged 8 to 17 years old, recruited as part of the Portuguese sibling study on growth, fitness, lifestyle, and health (see Pereira et al).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Niermann et al [55] used cluster analysis to identify patterns of health behaviors within families based on triads (father, mother, and child) and reported lower intraclass correlation values than in our sample. Furthermore, previous studies investigating sibling resemblance for each individual health-related marker, namely physical fitness [17,56,57], physical activity [58,59,60], body composition [61,62], and diet [63], showed low-to-moderate sibling similarities. However, the effect sizes of such sib-ships’ likeness varied across studies, which can also be partially explained by differences in sample sizes and composition, age range, reference population, analytical strategies, and covariate adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…The current study sample was from the Portuguese Sibling Study on Growth, Fitness, Lifestyle and Health, which investigates physical growth, body composition, physical fitness, physical activity, metabolic syndrome, and health behaviors in a cohort of siblings [17]. The subjects in this study were part of a larger study, the Portuguese Healthy Family Study [17], in which participants were randomly sampled from schools in mainland (north and central) Portugal and from the Azores islands. Those who had their siblings studying in the same school were invited to take part in the study (~4100), and the response rate was ~80%.…”
Section: Methodsmentioning
confidence: 99%